2017
DOI: 10.32734/jtk.v5i4.1555
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Ukuran Partikel, Waktu Dan Suhu Pada Ekstraksi Fenol Dari Lengkuas Merah

Abstract: Galangal is one of spices containing phenol. This study aims to product phenol in a liquid phase from galangal. The variations performed in this study involve the time of extraction (3 hours, 6 hours, 9 hours), temperature (30 oC, 45 oC, 60 oC) and particle size of raw material (70 mesh, 100 mesh, 140 mesh). One of the analysis in this study is the yield of phenol. The highest phenol in this study is about 4,5%. This result is obtained using 140 mesh of tray at 60°C of temperature and 9 hours of extraction tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…The value of viscosity solution was caused by the elevated of the extraction temperature, which then reduces the mass transfer resistance, so that the solid particle cell network softens and facilitates the transfer of the solute to the solvent [18]. This is to the research of Tambun et al [19] regarding the extraction of galangal which showed that a temperature of 60°C produced the highest total phenol. In addition, the results of Ananta et al [18] stated that the total phenol content will continue to increase for up to 36 hours, and will decrease at 48 hours of maceration The effect of time and temperature of extraction on velvet bean extract's total flavonoid compounds (TFC) can be seen in Figure 3.…”
Section: Measurement Of Tpc Tfc and Ttcmentioning
confidence: 99%
“…The value of viscosity solution was caused by the elevated of the extraction temperature, which then reduces the mass transfer resistance, so that the solid particle cell network softens and facilitates the transfer of the solute to the solvent [18]. This is to the research of Tambun et al [19] regarding the extraction of galangal which showed that a temperature of 60°C produced the highest total phenol. In addition, the results of Ananta et al [18] stated that the total phenol content will continue to increase for up to 36 hours, and will decrease at 48 hours of maceration The effect of time and temperature of extraction on velvet bean extract's total flavonoid compounds (TFC) can be seen in Figure 3.…”
Section: Measurement Of Tpc Tfc and Ttcmentioning
confidence: 99%
“…Ukuran partikel dari kayu gaharu merupakan salah satu faktor yang mempengaruhi proses ekstraksi. Pengecilan ukuran dapat memperluas permukaan bahan sehingga mempermudah pelarut untuk dapat melakukan penetrasi ke dalam kayu gaharu [16]. Jumlah perbandingan pelarut, dan lama waktu ekstraksi akan mempengaruhi jumlah yield.…”
Section: Metodologiunclassified
“…Sedangkan ukuran partikel halus > 40 mesh tidak berbeda dengan ukuran 0,1 -0,5 cm. Hasil ini menunjukkan bahwa adanya peningkatan pada yield sebesar 0,18% diakibatkan oleh pengecilan ukuran partikel yang berdampak pada semakin banyaknya poripori yang terbentuk sehingga terjadi peningkatan jumlah minyak atsiri yang mudah diserap [16] dan banyak partikel yang saling berekasi [12]. Akan tetapi pengecilan ukuran hingga >40 mesh tidak berdampak peningkatan yield minyak atsiri gaharu dan dapat menyebabkan penggumpalan sehingga sulit untuk permease pelarut [16].…”
Section: Kajian Pengaruh Ukuran Partikel Terhadap Yield Minyak Atsiriunclassified
See 1 more Smart Citation
“…Ultrasonic can also reduce the extraction temperature and can be used in the extraction of bioactive compounds that are not resistant to high temperatures (Zou et al, 2014). The research of Rondang Tambun et al (2017) stated that the phenol content of red galangal extract using ultrasonic was highest at 9 hours with a temperature of 60°C at 45%. In addition, Handayani, Sriherfyna and Yunianta (2015) research stated that antioxidant extraction in soursop leaves was best treated at 45°C in 20 minutes with a yield of 11.72%, total phenol content of 15,213.33 ppm, 45,843 ppm flavonoid content, and antioxidant activity of 78.14%.…”
Section: Introductionmentioning
confidence: 99%